Using an Imagery Intervention to Train Visual Exploratory Activity in Elite Academy Football Players. Issue 2 (3rd April 2019) - Pocock, Chris; Dicks, Matt; Thelwell, Richard C.; Chapman, Michael; Barker, Jamie B.
Abstract : Football players adapt their movements to opportunities within the surrounding environment by engaging in visual exploratory activity (VEA) to pick up information. This study adds to the extant literature by using a 6-week PETTLEP imagery intervention to train VEA and improve performance with the ball. A single-case, multiple baseline across participants' design was conducted with 5 elite academy football players. Results indicated that a PETTLEP imagery intervention improved VEA, particularly in center midfielders. In addition, indications of improvements in performance with the ball were present within some participants. Future researchers could examine the processes underpinning VEA to enhance applied interventions for this skill.